Integrating Artificial Intelligence in Home Economics Technology Education: Teacher Strategies for Digital Innovation - Janneka Fae Capuno-Marsan; Angelito Llena Marsan (The Indonesian Institute of Science and Technology Research, 2026)
This study investigated the integration of Artificial Intelligence (AI) in Home Economics instruction to foster digital innovation, efficiency, and sustainability. It specifically assessed the levels of AI literacy, self-efficacy, and self-management among 78 postgraduate students from one of the state universities in Cebu, Philippines, during the 2025–2026 academic year. Utilizing a descriptive-survey design, data were gathered via adapted Google Forms and analyzed using frequency, weighted mean, and Pearson r. Results indicated that respondents possessed a high level of AI literacy, particularly regarding ethical considerations and basic applications, though detection skills were lower. In contrast, self-efficacy and self-management were rated as moderate. This disparity suggests that while educators understand AI concepts, they lack the requisite confidence and regulatory skills to implement these tools effectively in classroom instruction. Statistical analysis revealed no significant relationship between AI literacy and either self-efficacy or self-management, implying that theoretical knowledge does not automatically translate into instructional confidence or pedagogical usage. The study concludes that technological awareness is insufficient for transformative digital innovation without corresponding psychological and managerial readiness. While literacy is established, the lack of correlation with confidence highlights a critical gap in professional application. Consequently, there is an urgent need for targeted professional development programs that move beyond basic literacy to foster practical competence. This research accentuates that institutional support must prioritize bridging the gap between understanding and the self-regulated execution of AI-driven strategies.